A case of auricular myiasis in Malaysia - Rohela, M.; Jamaiah, I.; Amir, L.; Nissapatorn, V. (2006)
Many cases of myiasis have been reported in Malaysia. This is the second reported case of auricular myiasis caused by Chrysomya bezziana. The patient was a 41-year-old, mentally retarded, Orang Asli man. He was brought to the clinic by his mother with a complaint of pain and bleeding in his right ear for 3 days. On examination, blood and multiple maggots were seen packed in the external auditory canal of the right ear. A total of 39 live maggots were removed and maintained until they developed into 3rd instar larvae, which were later processed and identified as Chrysomya bezziana. The patient was discharged with amoxicillin 500 mg three times a day for 1 week.